A new species of Aaptos (Porifera, Hadromerida, Suberitidae) from Pribilof Canyon, Bering Sea, Alaska - Lehnert, Helmut; Hocevar, John; Stone, Robert P. (Zootaxa, 2008)
The Bering Sea is predominantly a shallow sea, with a massive shelf mostly shallower than 100 m. Pribilof Canyon and Zhemchug Canyon, two of the largest submarine canyons in the world, were explored in August 2007, by the Greenpeace vessel “Esperanza”, with manned submersibles and a remotely operated vehicle (ROV) to depths of 1000 m. Specimens were collected with hydraulic manipulators operated by the pilots of the submersibles or with the ROV. Once on deck the specimens were transferred to ethanol. Pribilof Canyon is 426 km long and 1800 m deep, while Zhemchug Canyon is even larger and reaches depths of more than 2600 m (Normark and Carlson 2003). Here we describe a new species of Aaptos and compare it with representative congeners. The genus Aaptos was erected by Gray (1867) for Aaptos aaptos, described by Schmidt (1864) as Ancorina aaptos. Today, Aaptos is placed in Suberitidae Schmidt, 1870 and contains 21 species (Van Soest et al. 2005). For a more detailed historical review of the family and genus we refer to the publications of Kelly-Borges & Bergquist (1994) and to Van Soest (2002). According to Van Soest (2002), Aaptos is separated from other Suberitidae by its spherical or lobate growth forms, and by the presence of a strictly radial skeleton that contains characteristic strongyloxeas. The type species was described from the Mediterranean Sea (Algeria) and was then reported from many other areas of the world. These subsequent records likely represent additional undescribed species of Aaptos (Van Soest, 2002).